The direct plan of cali (2006)
This article is an approach to one of the projects of modern urbanism considered in Colombia in the middle of the 20th century, the Pilot Plan for Cali, designed by Town Planning Associates. Thanks to the recovery of the Plan original material, the author does a brief resume of the special circumstances that surrounded its elaboration and the main proposals of the project.